2003
DOI: 10.1046/j.1365-2982.2003.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnetic detection of gastric electrical activity in normal and vagotomized rabbits

Abstract: We recorded the vector magnetogastrogram (MGG) due to gastric electrical activity (GEA) in normal rabbits using a Superconducting QUantum Interference Device (SQUID) magnetometer and measured the degree of correlation of the MGG with 24 channels of serosal electrodes. The vector magnetometer allows us to non-invasively record three orthogonal magnetic field components and project the recorded magnetic field vector into arbitrary directions. We optimized the magnetic field vector direction to obtain the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…While an overall decrease in the slow wave frequency might suggest bradygastria, the additional changes we observed in the PPD, with signal power shifting into both brady-and tachygastric frequency ranges, suggest that glucagon induces more complicated rhythm disturbances in the gastric syncytium that could involve uncoupling, ectopic pacemakers, conduction pathway blocks, and/or reentry loops, similar to effects observed in diseased myocardium. We have observed similar PPD effects in mechanically uncoupled gastric tissue (2,29) and in vagotomized rabbits (6).…”
Section: Discussionsupporting
confidence: 68%
“…While an overall decrease in the slow wave frequency might suggest bradygastria, the additional changes we observed in the PPD, with signal power shifting into both brady-and tachygastric frequency ranges, suggest that glucagon induces more complicated rhythm disturbances in the gastric syncytium that could involve uncoupling, ectopic pacemakers, conduction pathway blocks, and/or reentry loops, similar to effects observed in diseased myocardium. We have observed similar PPD effects in mechanically uncoupled gastric tissue (2,29) and in vagotomized rabbits (6).…”
Section: Discussionsupporting
confidence: 68%
“…By projecting the magnetic field vector into different directions, we can focus on a particular feature of the signal or a particular signal frequency. We also showed that a single vector magnetometer was capable of reproducing electrical activity recorded by a 24-channel serosal electrode array with excellent fidelity [18]. Moreover, the magnetic field vector projection correlates to the direction of propagation of electrical activity the magnetic field is perpendicular to the direction of current.…”
Section: Biomagnetic Techniques To Assess Normal Geamentioning
confidence: 82%
“…Thus, the vector projection provides a substantial increase in the signal-tonoise ratio and aids in the discrimination of signals from multiple bowel sources. In another study, a single vector magnetometer produced projections that correlated highly with 24 gastric serosal electrodes and reflected spatiotemporal signal changes that occurred following a vagotomy [18]. This observation strongly suggests that additional information is available in the full vector recording of the gastrointestinal magnetic field as opposed to that available in any single component.…”
Section: Biomagnetic Techniques To Assess Gea Dysrhythmiasmentioning
confidence: 94%
“…Previous studies showed that the magnetogastrogram records signals with the same waveshape and frequency as slow waves recorded with internal serosal electrodes [15, 16]. In addition, studies show that slow wave propagation can be detected with multichannel magnetometers [17], and magnetogastrograms (MGG) propagation characteristics are altered in disease and by both mechanical and pharmacological uncoupling [18, 19]. …”
Section: Introductionmentioning
confidence: 99%